High speed synchrotron X-ray diffraction experiments resolve microstructure and phase transformation in laser processed Ti-6Al-4V. Issue 10 (3rd October 2021) - Oh, Seunghee A.; Lim, Rachel E.; Aroh, Joseph W.; Chuang, Andrew C.; Gould, Benjamin J.; Amin-Ahmadi, Behnam; Bernier, Joel V.; Sun, Tao; Pistorius, P. Chris; Suter, Robert M.; Rollett, Anthony D.
Abstract : The microstructures of Ti-6Al-4V following laser processing depend primarily on the phase transformation of β to α, but their development is constrained by the rapidly changing temperature in the small fusion zone. In-situ synchrotron X-ray diffraction was utilized to probe the rapid phase evolution in single melt tracks with high angular and temporal resolution. Both fully martensitic and mixed α+α′+β microstructures were confirmed by microscopy. Cooling rates were inferred from the lattice parameter history and complementary thermal simulation. It was found that the threshold cooling rate for fully martensitic transformation is in the range between 2900 and 6500°C/s. IMPACT STATEMENT: High-speed synchrotron X-ray diffraction during operando laser processing suggests a new threshold between martensitic and diffusional phase transformation in Ti-6Al-4V occurring at higher cooling rates than previously reported.